Frekuensi Resistensi pada Enterococcus faecalis Terhadap Dekokta Rosella (Hibiscus sabdariffa Linn) dan Antibiotik Amoksisilin - Putri Lissanawidya; Rio Risandiansyah; Hardadi Airlangga (Published by Faculty of Medicine Universitas Islam Malang, 2017)
Introduction: The inappropriate use of antibiotics leads to antibiotic resistance. This can be supported by measuring resistance frequency of bacteria to antibiotics. Antibacterial activity is also found in many herbal medicines consumed as a traditional medicine, therefore resistance is suspected to occur in herbal medicine. This study aims to measure the frequency of resistance in Enterococcus faecalis applied to againts Rosella (Hibiscus sabdariffa Linn) decocta. The method used will also be applied to Amoxicillin as a control. Method: Disc diffusion method was used to the measure inhibition zone (ZOI). Dilusion method used for minimum inhibition concentration (MIC). Resistance frequency was tested using Luria-Delbrück method, using 5 plates and 2 controls performed in 3 repetitions. Results were measured statistically using Mann Whitney U Test (p ≤ 0.05). Results: The ZOI from Rosella decocta and Amoxicillin was 20 mm at each concentration of 250 mg/ml and 200 mg/ml, respecticly MIC from Rosella decocta was 3,125 mg/ml, whereas Amoxicillin used the MIC from literature (0,00902 mg/ml). From 3 repetition, 1 coloni was found to be resistance to Rosella decocta on repetition 2 and the resistance frequency was 7,8 x 10-12 mutant per total population cell. Amoxicillin was calculated the resistance frequency from 3 repetition which was 1,2-1,8 x 10-2mutant per total population cell. The data was tested statistically and showed that there is a significant difference between the resistance frequency of Enterococcus faecalis towards Rosella decocta resistance and Amoxicillin resistance. Conclusion: From this study it can be concluded that the use of Rosella herbal as a traditional medicine, especially for antibacterials has a low resistance frequency of mutation. Therefore, resistance to Rosella decocta cannot occurred in short term. Keywords: Resistance, Luria-Delbrück Method, Resistance Frequency, Rosella (Hibiscus sabdariffa Linn).